Letter: limitations of defecography among patients with refractory constipation. Authors' reply. Issue 1 (11th June 2019) - Grossi, Ugo; Di Tanna, Gian Luca; Heinrich, Henriette; Taylor, Stuart A.; Knowles, Charles H.; Scott, S. Mark
Abstract : Linked Content This article is linked to Grossi et al and Basilisco and Corsetti papers. To view these articles, visithttps://doi.org/10.1111/apt.15039 andhttps://doi.org/10.1111/apt.15289 .